Evaluasi Implementasi Good Governance dalam Sistem Administrasi Negara Indonesia: Analisis Faktor Penghambat dan Strategi Optimalisasi - Jumiati, Jumiati; Ikmal, Rayhan Raffatta; Aziz, Hafizul; Ilzahra, Aina; Bako, Yudika; Saputra, Boni (Jurnal Ilmu Sosial, Humaniora dan Seni, 2025)
The implementation of good governance in Indonesia's public administration system is a crucial element in realizing an effective, transparent, accountable and responsive government. This research aims to analyze the extent to which the principles of good governance have been applied in the implementation of public administration in Indonesia, as well as the challenges and obstacles faced in the implementation process. The method used is a qualitative approach with literature study and policy analysis. The results of the study show that although some principles such as public participation, transparency, and accountability have begun to be applied, their implementation is still partial and uneven in all government institutions. Factors such as a bureaucratic culture that has not fully changed, weak supervision, and low governance literacy among the apparatus are the main obstacles. Therefore, more consistent bureaucratic reforms, strengthening institutional capacity, and high political commitment are needed to realize a state administration system that is in line with the principles of good governance.